Ruling out unitary Fermi gas of neutrinos as galactic dark matter - Aceña, Andrés Esteban (2024)
We investigate the possibility that galactic dark matter could be interacting fermions in the neutrino mass range. Assuming that galactic halos behave like a fluid in hydrostatic and thermal equilibrium, we employ the equation of state for a unitary Fermi gas to establish constraints on the mass of the fermion. Our findings effectively exclude neutrinos as candidates for galactic dark matter, and further reinforce earlier results suggesting that galactic dark matter is predominantly composed of light bosons.